PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (CSR) PERBANKAN SYARIAH BERDASARKAN ISLAMIC SOCIAL REPORTING INDEX (INDEKS ISR) - Nurhayati, Nurhayati (JAAKFE UNTAN (Jurnal Audit dan Akuntansi Fakultas Ekonomi Universitas Tanjungpura), 2017)
This research was conducted by analyzing how the Islamic Bank (BSM) reports corporate social responsibility. The results of this study indicate that Bank Syariah Mandiri has implemented the six themes in Islamic Social Reporting, namely the Theme of Funding and Investment (Finance & Investment), Products and Services (Product and Services), Employees (Employees), Community (Community involvement), Environment (Environment), Corporate Governance. Only in the disclosure there are several items from the theme of corporate governance that are not disclosed, the item is the Anti- corruption and Anti-Terrorism Policy.Keywords: Corporate Social Responsibility, Islamic Bank, Islamic Social Reporting, Bank Syariah Mandiri